PEMBINAAN PERENCANAAN KEUANGAN DAN INVESTASI BAGI GURU DAN KARYAWAN BPK PENABUR BANDAR LAMPUNG - Anatan, Lina; Martalena; Iskandar, Dini; Wahyusaputra, Tedy; Herlina (Servirisma, 2024)
The global economic crisis challenge which caused the economy to not be conducive had a significant impact on the macroeconomic and microeconomic levels, namely individuals. In this circumstance, the public needs to be provided education related to financial literacy, especially financial planning, investment, and retirement through community service activities. Implementation of community service activities in the form of training is conducted to provide information and knowledge and increase public understanding, especially teachers and employees of BPK Penabur Bandar Lampung on the importance of financial planning, investment planning, and retirement planning. The evaluation results pre- and post-presentation of material related to these three topics showed an increase in participants' understanding of financial planning, investment planning and retirement planning. Apart from that, there has been an increase in information and access to knowledge related to financial planning, investment planning, especially related to investment instruments, and retirement planning. These two conclusions were drawn based on evaluation results which showed an increase in the percentage of correct answers given by participants.